2015
DOI: 10.1063/1.4936398
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy of Mn doped ZnO thin films prepared by rf sputtering technique

Abstract: A set of r.f. sputter deposited ZnO thin films prepared with different Mn doping concentrations have been characterised by Extended X-ray Absorption Fine Structure (EXAFS) and X-ray Absorption Near Edge Spectroscopy (XANES) measurements at Zn, Mn and O K edges and at Mn L2,3 edges apart from long range structural characterisation by Grazing Incident X-ray Diffraction (GIXRD) technique. Magnetic measurements show room temperature ferromagnetism in samples with lower Mn doping which is however, gets destroyed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
2
7
2
Order By: Relevance
“…In summary, Mn incorporation into the ZnO structure was confirmed from the XANES and EXAFS fitting. These results match well with those shown by Yadav et al (2015).…”
Section: Figuresupporting
confidence: 92%
“…In summary, Mn incorporation into the ZnO structure was confirmed from the XANES and EXAFS fitting. These results match well with those shown by Yadav et al (2015).…”
Section: Figuresupporting
confidence: 92%
“…On the other hand, the superparamagnetic behavior observed in LTO:Fe-HC is associated with the high Fe concentration (above 10 at.%) found on the thin film, where the synthesis conditions promoted the generation of the magnetic behavior. It has been reported that high amounts of dopant destroy the ferromagnetic order in DMOs and other types of magnetic behavior may arise [53][54][55][56]. In our case, the LTO:Fe-HC sample presented a superparamagnetic behavior.…”
Section: Magnetic Properties Of the Lto:fe-hc And Lto:fe-lc Thin Filmssupporting
confidence: 45%
“…The appearance of ferromagnetism in DMOs has been reported for dopant concentrations of up to 10 at.% [52]. However, it has been reported in the literature that there is a maximum limit of dopant concentration (which varies for each material) above which the ferromagnetic ordering begins to decrease and even gets destroyed [53][54][55][56].…”
Section: Magnetic Properties Of the Lto:fe-hc And Lto:fe-lc Thin Filmsmentioning
confidence: 99%
“…38 Oxygen vacancy mediated FM has been observed by us in several other doped TM doped ZnO samples also viz., in Fe doped and Cr doped ZnO nanocrystals and Mn doped ZnO thin lm samples. [39][40][41]…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%